Pentingnya Evaluasi Penilaian Kinerja - M. Arif Pratama Manurung; Aswaruddin Aswaruddin; Laudy Livianti; Cendani Alfanizha Hidma; Nur Siti Maysarah; Indah Wahyuni (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This research aims to recognize the importance of performance appraisal evaluations on employee development. This research uses literature review procedures (library research). This research aims to provide an in-depth understanding of how the integration of performance assessment evaluations can contribute directly to employee professional growth and, ultimately, provide comprehensive benefits for the development of the organization as a whole.